World after - Ee, Susan (Ee, Susan. Penryn & the end of days ;, 2013)
Penryn's search for her kidnapped sister, Paige, leads her into the heart of the angels' secret plans, while Raffe must choose between reclaiming his wings--and his role as the angels' leader--or helping Penryn survive.